Changes in Body Composition and FTO Whole Blood DNA Methylation Among Japanese Women: A Randomized Clinical Trial of Weight-Loss Program - Nishida H (Dove Medical Press, 2020)
Haruhiko Nishida,1 Katsuko Onishi,1 Satoshi Kurose,1 Hiromi Tsutsumi,1 Takumi Miyauchi,2 Nana Takao,2 Sawako Yoshiuchi,2 Aya Fujii,2 Yutaka Kimura1,2 1Department of Health Science, Kansai Medical University, Osaka, Japan; 2Health Science Center, Kansai Medical University, Osaka, JapanCorrespondence: Haruhiko NishidaDepartment of Health Science, Kansai Medical University, 2-5-1 Shinmachi, Hirakata, Osaka 573-1010, JapanTel +81 72 804 2334Fax +81 72 804 2548Email nishidah@hirakata.kmu.ac.jpObjective: DNA methylation is an epigenetic mechanism that regulates gene expression. The obesity-related (FTO) gene is the first gene found to be associated with fat mass and obesity. However, no studies have examined the relationship between weight-loss intervention effect and FTO methylation in obese individuals with whole blood DNA. The purpose of this study was to quantify FTO whole blood DNA methylation and investigate the relationship between body composition, exercise capacity, and blood parameters with a 6-month weight-loss program intervention.Participants and Methods: Eighteen female participants (mean age, 50.6 ± 12.1 years, body mass index (BMI), 33.5 ± 6.2 kg/m2) who completed a 6-month weight-loss program at the obesity outpatient department at the Health Science Center of Kansai Medical University Hospital from March 2017 to October 2018 were included in the analysis. Participants were randomized into a normal treatment group (NTG) and a group with additional resistance training (RTG). Body composition, exercise tolerance and metabolic index were measured in each participant. DNA methylation status in whole blood samples was determined using pyrosequencing. All measurements were taken during the first visit and at the 6-month post-intervention visit.Results: The methylation rate was significantly decreased in the NTG in CpG1 (p=0.011) and total value of CpG (p=0.011), whereas in the treatment group containing resistance training (RTG), CpG3 (p=0.038) was increased significantly. Furthermore, the independent factors that determine %CpG3 of RTG were visceral fat area change rate (%VFA) (β = − 0.568, P = 0.007, R2 = 0.527) and resistance training (β = 0.517, P = 0.012, R2 = 0.527), which have been extracted.Conclusion: A 6-month weight-loss program, including resistance training, may be associated with decreased visceral fat area changes and increased RTG CpG3 methylation changes. However, further replication studies with larger sample sizes are warranted to verify the findings of this study.Keywords: epigenetics, obesity, body composition, resistance training